Students Learning Research Process in Fashion Design in the Context of Sustainability: Development of New Products from Non-traditional Materials - Mežinska, Silvija; Baniene, Jolanta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The article analyzes one of the most pressing problems of waste-utilization. In other words looking at nearby objects, taking into account the long-term evolution of the planet. Introducing the processing facilities, promotion of unexpected and interesting design solutions, providing unnecessary items on a „second breath”. It is shown that environmental friendliness is not boring or very difficult, but interesting and promising. An introduction to students, setting up a facility to learn how to apply the principles of composition, artistic expression and harmonization measures, and learn about the design and manufacturing technology, new materials, original techniques and learn to creatively apply knowledge and professional practice. In particular, attention is drawn to high-quality and thorough completion of tasks. The aim of the study: sustainability awareness and development of the research competence of prospective designers, exploring the usage of non-traditional material within professional fashion design and design studies in the context of sustainability. The methods of research- theoretical -analysis of the literature, empirical – qualitative research methods such as the analysis of the study tasks implemented by the Rezeknes Augstskola and Utenos Collegia study programs “Clothes design and technology”, observation and analysis of students’ creative activity.